Homoeopathic Silicea a Novel Elicitor to Enhance Secondary Metabolite Production in Micro propagation of Psoralea Corylifolia (Advancements in Homeopathic Research, 2025)
Background and Objectives : Psoralea corylifolia Linn., an endangered medicinal plant with bioactive compounds, faces propagation challenges due to low rates of seedling emergence and high mortality of seedlings. This study aims to address these challenges using in vitro techniques and explores the use of homoeopathic Silicea to enhance secondary metabolite production, combining modern micropropagation and agrohomoeopathy for sustainable therapeutic potential. Methods: Homoeopathic medicine Silicea in various potencies (6CH, 12CH, 30CH, 200CH, 1M) was evaluated for its effectiveness in enhancing the production of secondary metabolites during the micropropagation of Psoralea corylifolia. The percentage of callus induction and the quantity of psoralen were determined and compared with positive controls, which included Auxin/Cytokinin treatment groups with different 2,4-D concentrations alone, and in combination with BAP or KN. Results: Homoeopathic medicine Silicea in different potencies (6CH, 12CH, 30CH, 200CH, 1M) were screened and found that the average % of callus induction tends to increase with the potency of Silicea. The highest average % of callus induction is observed for 1M and 200CH potency Silicea, while the lowest is seen for 6CH, 12 CH, and 30CH Silicea. The highest average psoralen quantity area was observed for 1M, but it was not statistically significantly different from 200CH and 30CH potency. Conclusion: Increasing the potency of Silicea from 6CH to 1M leads to a significant increase in the average psoralen quantity area. Hence, we can conclude that the homoeopathy medicine Silicea has the potential to increase the average psoralen quantity area.
Keywords: Callus induction; Homoeopathy; Micropropogation; Plant tissue culture; Psoralea corylifolia L.; Psoralen Quantity; Secondary metabolite; Silicea